Coping Strategies In Overcoming Academic Stress Among High School Students - Handayani, Fitriah; Jonathan, Bouyea; Joshuar, Wang; Mark, Eladdadi; Halim, Chandra (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Academic stress is a problem often faced by high school students, it can affect their mental well-being and academic performance. Coping strategies play an important role in helping students deal with such stress. This study aims to explore various coping strategies used by high school students in dealing with academic stress and its impact on their mental well-being. This research uses a qualitative approach. Data were analyzed using the thematic analysis method to identify patterns of coping strategies used. The results of this study indicate that high school students use various coping strategies to deal with academic stress, such as social support from peers, exercise, and relaxation techniques such as meditation. Students also use problem-solving and cognitive restructuring strategies to change their perceptions of academic stressor situations. The conclusion of this research is that the coping strategies used by high school students play a very important role in helping them overcome academic stress and improve mental well-being. The importance of providing approaches in managing academic stress among students to promote their mental health. This research provides valuable insights for educators and counselors to develop appropriate interventions to support students to deal with academic stress more effectively.